Multiscale investigation of shear relaxation in shock loading: A top-down perspective. (August 2022) - Liu, Jingnan; Liu, Guisen; Ye, Changqing; Chen, Kaiguo; Hu, Jianbo; Yu, Yuying; Shen, Yao
Graphical abstract: Highlights: A perspective on the multiscale origin of shear relaxation at the shock front is obtained through a top-down approach . Strain rate hardening effect is the direct cause of shear relaxation, with the critical condition of ε ̇ p > 2 / 3 ∙ ε ̇ 1 . Other factors play minor roles, e.g., limited effects of temperature rise, deformation heterogeneity and strain hardening. Abstract: Shear relaxation commonly occurs in shock compressed metals at the plastic wave front, but no consensus has ever been reached on its origin due to the multiscale nature of high rate plasticity. To this end, this work takes a top-down approach by conducting a theoretical and numerical investigation on the macroscale, and then simulations on the mesoscale with crystal plasticity, followed by a brief discussion on the microscale mechanisms based on dislocation theory. On the macroscale, theoretical derivation through isotropic elasticity and von-Mises plasticity, as well as continuum simulations of shocked aluminum employing Johnson-Cook plasticity and equations of state for nonlinear elasticity at high pressures, uncovers that strain rate hardening decisively leads to shear relaxation when the equivalent plastic strain rate is greater than two-thirds of the total strain rate ( ε ̇ p > 2 / 3 ∙ ε ̇ 1 ). Other factors play subsidiary roles, including limited or conditioned promotive effect of thermal softening and suppressive effect of strain hardening. On the mesoscale, simulations with crystal plasticity and hyperelasticity perfectly verify the macroscopic discoveries, and additionally revealed the subordinate stimulative effect of deformation heterogeneity of polycrystals. On the microscale, dislocation nucleation and multiplication are identified as the dominant factors by evaluating contributions of micro-mechanisms to strain rate hardening.